2014
DOI: 10.1111/febs.12734
|View full text |Cite
|
Sign up to set email alerts
|

N‐methylmesoporphyrin IX fluorescence as a reporter of strand orientation in guanine quadruplexes

Abstract: Guanine quadruplexes (GQ) are four‐stranded DNA structures formed by guanine‐rich DNA sequences. The formation of GQs inhibits cancer cell growth, although the detection of GQs in vivo has proven difficult, in part because of their structural diversity. The development of GQ‐selective fluorescent reporters would enhance our ability to quantify the number and location of GQs, ultimately advancing biological studies of quadruplex relevance and function. N‐methylmesoporphyrin IX (NMM) interacts selectively with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 45 publications
(64 reference statements)
9
98
0
Order By: Relevance
“…The sequences of S2 M1 and S2 M2 are 5′‐GGGACGGG‐3’ and 5′‐GTGGAGGG‐3′, respectively. As shown in Figure S2 (Supporting Information), the NMM fluorescence was weakly sensitive to pH over a range from 5.2 to 8.0, which is in line with the previous results . When NMM was incubated with S2 M1 and S2 M2, the NMM fluorescence increased slightly and remained insensitive to pH changes in the absence of K + .…”
Section: Methodssupporting
confidence: 90%
“…The sequences of S2 M1 and S2 M2 are 5′‐GGGACGGG‐3’ and 5′‐GTGGAGGG‐3′, respectively. As shown in Figure S2 (Supporting Information), the NMM fluorescence was weakly sensitive to pH over a range from 5.2 to 8.0, which is in line with the previous results . When NMM was incubated with S2 M1 and S2 M2, the NMM fluorescence increased slightly and remained insensitive to pH changes in the absence of K + .…”
Section: Methodssupporting
confidence: 90%
“…2A) (18), and distinct from a control sequence (sequence 42) that had poor chaperone activity and no polyG motif. This supposition was further supported by examining the emission spectra of Nmethylmesoporphyrin IX (NMM), a well characterized parallel quadruplex binding fluorophore (19,20). The NMM spectra indicated that all three sequences formed parallel quadruplexes at the concentration used in aggregation assays, unlike the ssDNA control ( Fig.…”
Section: G-quadruplexes As Potent Holdasesmentioning
confidence: 86%
“…N-methylmesoporphyrin IX (NMM) Fluorescence NMM is a well characterized fluorophore that increases fluorescence when bound to parallel quadruplexes (19). The emission spectra of 10 μM NMM was measured using an excitation wave length of 399 nm, and an emission range of 550 to 750 nm in the presence of 1 μM DNA.…”
Section: Chemical Aggregationmentioning
confidence: 99%
“…S4. NMM is an anionic porphyrin with a good structural selectivity for G-quadraplex313233. It has weak fluorescence signal by itself, but exhibits a dramatic fluorescence enhancement after binding to G-quadruplex.…”
mentioning
confidence: 99%